Competitive Advertising and Pricing - Hwang, Ilwoo; Kim, Kyungmin; Boleslavsky, Raphael (Review of Economic Studies, 2026)
Abstract We consider an oligopoly model in which each firm chooses not only its price but also its advertising strategy regarding how much, and what, product information to provide. To highlight firms’ strategic incentives, we impose no structural restrictions on feasible advertising content, so that each firm can disclose or conceal any information. We obtain a comprehensive characterization of the equilibrium advertising strategy and provide some sufficient conditions for the existence of symmetric pure-price equilibria. We show that intense competition induces firms to provide accurate product information; firms usually obfuscate consumers’ relatively low or high values; and requiring firms to provide more product information can reduce social surplus and also be harmful to consumers.